2000
DOI: 10.1006/viro.1999.0062
|View full text |Cite
|
Sign up to set email alerts
|

Creation and Repair of Specific DNA Double-Strand Breaks in Vivo Following Infection with Adenovirus Vectors Expressing Saccharomyces cerevisiae HO Endonuclease

Abstract: To study DNA double-strand break (DSB) repair in mammalian cells, the Saccharomyces cerevisiae HO endonuclease gene, or its recognition site, was cloned into the adenovirus E3 or E1 regions. Analysis of DNA from human A549 cells coinfected with the E3::HO gene and site viruses showed that HO endonuclease was active and that broken viral genomes were detectable 12 h postinfection, increasing with time up to approximately 30% of the available HO site genomes. Leftward fragments of approximately 30 kbp, which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 70 publications
2
33
0
Order By: Relevance
“…Coinfection of 293 cells with both viruses results in cleavage of the HO site to steady state levels of some 10 to 30% of the total viral genomes (data not shown), similar to that observed with the original AdE1::HO site virus. 13 Approximately 18 hours after infection of 293 cells under low m.o.i. condition, RCA was performed directly on 8-well culture slides.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Coinfection of 293 cells with both viruses results in cleavage of the HO site to steady state levels of some 10 to 30% of the total viral genomes (data not shown), similar to that observed with the original AdE1::HO site virus. 13 Approximately 18 hours after infection of 293 cells under low m.o.i. condition, RCA was performed directly on 8-well culture slides.…”
Section: Resultsmentioning
confidence: 99%
“…Introduction of yeast HO endonuclease and its recognition site into cultured mammalian cells makes it possible to induce sequencespecific DNA DSBs. 13 The unique identification of RCA signals in cultures doubly infected with viruses carrying endonuclease and cleavage sites, and the nuclear localization of these signals, suggests that the sites of RCA were indeed sites of DSBs induced by this system. We also demonstrated that in situ RCA and immunofluorescence…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional analyses show that ORF6, although not ORF3, can inhibit V(D)J-joining (Boyer et al, 1999), a process that requires DNA PK. Moreover, Young and coworkers showed that both ORF3 and 6 can inhibit the repair of speci®c double-strand breaks induced by the Saccharomyces cerevisiae HO endonuclease in co-infected cells (Nicola s et al, 2000).…”
Section: E4 Orf3 and E4 Orf6mentioning
confidence: 99%